Determinants of Customer Satisfaction in Internet Banking in Haryana - Monika Dahiya,; Dr. Mahipal Singh, (International Journal of Scientific Research in Science and Technology, 2025)
The rapid evolution of digital technology has transformed the banking industry, with internet banking emerging as an essential service in India. Haryana, a state with diverse socio-economic demographics, has witnessed a significant rise in internet banking adoption, driven by increased digital literacy, improved internet accessibility, and user-friendly banking applications. This study examines the determinants of customer satisfaction in internet banking within Haryana, focusing on three key functional factors: reliability, website efficiency, and transaction security. Additionally, it explores the impact of demographic variables, including age, gender, occupation, and income, on customer satisfaction levels. Through a structured survey conducted among 600 internet banking users, this study identifies the primary drivers of satisfaction and the factors influencing customer retention and loyalty. The findings reveal that while website efficiency and reliability contribute to satisfaction, transaction security has the most significant impact on customer trust and long-term engagement. Users who feel secure in conducting online transactions demonstrate higher loyalty levels and are more likely to continue using digital banking services. The study also highlights that younger and urban users report higher satisfaction, whereas older and rural users face challenges related to security concerns and digital literacy. The study concludes that banks must adopt a customer-centric approach, integrating advanced security measures, ensuring seamless website efficiency, and offering personalized services tailored to different demographic needs. By addressing these aspects, banks can enhance customer satisfaction, foster loyalty, and strengthen the digital banking ecosystem in Haryana. The study's insights provide valuable guidance for financial institutions seeking to improve their digital offerings and customer experience in an increasingly competitive market.
Keywords: Internet Banking; Customer Satisfaction; Transaction Security; Reliability; Website Efficiency; Demographic Influences; Haryana; Digital Banking